MISKIN MENURUT PANDANGAN AL-QUR’AN - Fauzi Arif Lubis (TANSIQ: Jurnal Manajemen Dan Bisnis Islam, 2018)
Poverty is a complex and multidimensional social problem. Facing this acute social problem, the Qur'an explains the terms and how to solve poverty problems. Therefore this study aims to find out the meaning of poverty. The approach in this study uses a descriptive approach by reducing data, presenting and concluding data. As for the results in the study that poverty in the view of the Qur'an is more dominant structural than cultural. This means that poverty is caused more by a system of social and political structures. Because poverty is more dominant in its structural nature, the Qur'an provides a multidimensional solution in order to overcome it, namely in the form of endeavors for each individual, taa'wun (help to help) fellow human beings through the ZISWAF concept and the form of cooperation contract, then the role of government in providing and encourage the availability of opportunities for those who want to improve their standard of living). The Qur'an builds motivation for social care, requires responsibility and social security both in terms of ethics and in terms of means of social care application, fair wealth distribution, law enforcement, and warns of the negative effects of poverty and mental fear of poverty.